2018
DOI: 10.3389/fmicb.2018.00161
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genomic Traits of Non-toxigenic Vibrio parahaemolyticus Strains Isolated in Southern Chile

Abstract: Vibrio parahaemolyticus is the leading cause of seafood-borne gastroenteritis worldwide. As reported in other countries, after the rise and fall of the pandemic strain in Chile, other post-pandemic strains have been associated with clinical cases, including strains lacking the major toxins TDH and TRH. Since the presence or absence of tdh and trh genes has been used for diagnostic purposes and as a proxy of the virulence of V. parahaemolyticus isolates, the understanding of virulence in V. parahaemolyticus str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 88 publications
0
41
0
Order By: Relevance
“…For instance, almost 80% of clinical V. parahaemolyticus strains contain filamentous phages, encoding the zona occludens toxin (Zot) (22). Also, non-human pathogens, such as V. coralliilyticus and V. anguillarum contain prophage-like elements encoding Zot, suggesting frequent horizontal gene transfer (HGT) of Zot via prophages among vibrios (11). In the present study, we found one filamentous phage, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, almost 80% of clinical V. parahaemolyticus strains contain filamentous phages, encoding the zona occludens toxin (Zot) (22). Also, non-human pathogens, such as V. coralliilyticus and V. anguillarum contain prophage-like elements encoding Zot, suggesting frequent horizontal gene transfer (HGT) of Zot via prophages among vibrios (11). In the present study, we found one filamentous phage, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, two phages VfO4K68 and VfO3K6 that carry the zona occludens toxin (Zot) and the accessory cholera enterotoxin (Ace), have been isolated from V. parahaemolyticus (4, 5). Zot and Ace are particularly common among vibriophages isolated from human pathogens, such as V. cholerae and V. parahaemolyticus (6-8) but are also present in prophage-like elements of non-human pathogens such as V. coralliilyticus (9) and V. anguillarum (10), suggesting frequent HGT among different vibrio species (11).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study showed that some strains of Vibrio parahaemolyticus lacking the classical toxins TDH and TRH possess genomic islands and prophage elements containing RTX, Zot and Ace toxins. Zot has also been found in prophage f237 of the pandemic strain and in prophage-like elements in V. coralliilyticus and V. anguillarum , suggesting that the horizontal gene transfer (HGT) associated to phages coding zot occurs frequently among Vibrio species ( Castillo et al, 2018 ). If pathogenicity genes are combined by HGT at high frequency the probability of generate new virulent species increases ( Nishibuchi and Kaper, 1995 ), which is favored in estuaries and marine environments which represent a extensive pool of virulence genes associated to species of the genus Vibrio ( Ceccarelli et al, 2013 ; Khouadja et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently the leading cause of seafood-borne diseases, and is gradually impacting global public health (Drake et al, 2010;Letchumanan et al, 2014). It is widely disseminated in estuarine areas, with epidemic outbreaks typically occurring in coastal countries and tropical and temperate regions (Alam et al, 2002;Gil et al, 2007;Ansaruzzaman et al, 2008;Castillo et al, 2018). Seafood-associated infections by V. parahaemolyticus were initially reported in Japan in the early 1950s (Ansaruzzaman et al, 2008), and their incidence has increased not only in coastal countries in which the temperature of seawater is warm, but also in cold northern regions (Velazquez-Roman et al, 2014;Soto-Rodriguez et al, 2015;Xu et al, 2016).…”
mentioning
confidence: 99%
“…The main virulence factors of V. parahaemolyticus are thermostable direct hemolysin (TDH) and TDH-related hemolysin (TRH) (Castillo et al, 2018), which are encoded by the tdh and trh genes, respectively (Ceccarelli et al, 2013;Raghunath, 2014). V. parahaemolyticus isolates containing tdh and/or trh are generally regarded as a public health threat (Broberg et al, 2011;Ceccarelli et al, 2013;Zhang and Orth, 2013) and food contaminated by these strains have the potential to cause human illness (Pazhani et al, 2014;Xie et al, 2017).…”
mentioning
confidence: 99%